2012
DOI: 10.1097/gme.0b013e31823b8983
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and topical hormone therapies reduce vaginal innervation density in postmenopausal women

Abstract: Objective Menopause is often accompanied by vaginal discomfort including burning, itching, dryness and spontaneous or provoked pain. While direct effects of estrogen withdrawal on vaginal cells are implicated, surgical menopause in rodents causes autonomic and sensory nerves to proliferate, suggesting that indirect effects mediated by changes in vaginal innervation may contribute. We assessed whether post-menopausal women display hormone-dependent changes in vaginal innervation. Methods Vaginal biopsies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
2
43
0
6
Order By: Relevance
“…Affected populations include TH-ir sympathetic, VIP-ir presumptive parasympathetic axons, and non-adrenergic, non-cholinergic (NANC) fibers that presumably represent both peptidergic (i.e., CGRP-ir) and non-peptidergic afferent fibers. Interestingly, topical HRT is significantly more effective than systemic HRT in reducing vaginal innervation (Griebling et al, 2012), which is consistent with the idea that estrogen's effects are due to direct actions on the target tissue rather than being secondary to effects. It should be noted that some indices of vaginal innervation do change as a function of cyclic changes in reproductive hormone levels including nociceptive threshold (Cason et al, 2003) and neuropeptide receptor transcripts (Dangoor et al, 2005).…”
Section: Remodeling Of Reproductive Tract Innervation By Sex Hormosupporting
confidence: 79%
“…Affected populations include TH-ir sympathetic, VIP-ir presumptive parasympathetic axons, and non-adrenergic, non-cholinergic (NANC) fibers that presumably represent both peptidergic (i.e., CGRP-ir) and non-peptidergic afferent fibers. Interestingly, topical HRT is significantly more effective than systemic HRT in reducing vaginal innervation (Griebling et al, 2012), which is consistent with the idea that estrogen's effects are due to direct actions on the target tissue rather than being secondary to effects. It should be noted that some indices of vaginal innervation do change as a function of cyclic changes in reproductive hormone levels including nociceptive threshold (Cason et al, 2003) and neuropeptide receptor transcripts (Dangoor et al, 2005).…”
Section: Remodeling Of Reproductive Tract Innervation By Sex Hormosupporting
confidence: 79%
“…Griebling, Liao, and Smith (2012) found that postmenopausal women not receiving any HT had relatively high levels of innervation, the majority of axons expressing tyrosine hydroxylase (indicating nor-adrenergic sympathetic fibres associated mainly with smooth muscle of the vasculature and muscles) or VIP (vasoactive intestinal peptide expressed by cholinergic parasympathetic innervation associated predominantly with vascular and non-vascular smooth muscle). Some 20% of axons were non-cholinergic, non-adrenergic (NANC) presumed to be the unmyelinated sensory innervation which also showed decreases with the hormonal treatments but their small number did not allow quantitative analysis.…”
Section: Vaginal Changesmentioning
confidence: 98%
“…Estrogen receptors present in the central and peripheral nervous systems are known to infl uence all aspects of neural activity from membrane permeability to gene regulation. The transition into menopause, with the accompanying change in systemic estrogen concentration, may therefore affect chronic pain [ 22 ].…”
Section: Vulvodynia and Menopause: Physiological Considerationsmentioning
confidence: 99%